The Effect of Proximal Femoral Nail and Position in the Femur on Clinical and Radiological Outcomes of Intertrochanteric Fractures - Levent Horoz; Mehmet Fevzi Çakmak (Sakarya Tıp Dergisi)
Purpose: Intramedullary nail treatment for intertrochanteric fractures has gained widespread popularity in recent years. Predisposing factors for mechanical failure of the proximal femoral nail include lag screw position, tip apex distance, reduction quality, and the femoral neck/shaft angle (FNSA). Our study aimed to evaluate the effect of the position of the nail end on the mechanical failure rates and radiological parameters. Method: The data of 118 patients who underwent proximal femoral nail repair due to intertrochanteric fractures were analyzed between June 2019 and September 2022. The patients were divided into three groups according to the proximal femoral nail end positioning of the femoral canal, and tip apex distance, FNSA, reduction quality, lag screw position, union time, and complications were evaluated on postoperative and follow-up radiographs. Results: When all patients included in the study were evaluated, cut-out was observed in 9. The cut-out rates were significantly higher in the medial group (n=7, p=0.003). Regarding FNSA, there were statistically significant differences among all three groups (<0.001M-S, M-L, S-L). In the medial group, the superiorly located lag screw, and in the lateral group, the inferiorly located lag screw was higher than in the other groups(p<0.001) Conclusion: It has been observed that placement of the distal tip of the nail in the canal affects both these parameters and clinical results, and the clinical and radiological results were worse in cases where the distal nail was medial to the canal.